Pengaruh Siaran RRI terhadap Sistem Pertahanan Non-Militer dan Dampaknya terhadap Perekonomian Nasional - Rahayu, Ayu Budi; Suwito, Suwito; Haetami, Haetami (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
National resilience in the era of information disruption faces serious challenges in the form of increasing disinformation flows, weakening social cohesion, and the potential for socio-political conflicts that have an impact on economic stability. The background of the issue underscores the importance of the strategic role of public broadcasting media in supporting Indonesia's non-military defense system. This study aims to analyze the contribution of Radio Republik Indonesia (RRI) to strengthen non-military defense and evaluate its relationship with national economic stability. This study uses a descriptive qualitative approach through a literature study, with a conceptual framework based on the AGHT (Threat, Disruption, Obstacle, Challenge) model and Early Warning Mechanism (EWM). Data is collected from relevant secondary sources, including policy documents, academic publications, and related institutional reports. The results of the study show that RRI plays a role as a trusted public information channel in building awareness of defending the country, strengthening social integration, and countering disinformation narratives that have the potential to trigger instability. The existence of RRI in border areas and conflict-prone areas shows its effectiveness in maintaining national cohesion. RRI creates a communication climate conducive to social and economic stability. The conclusion of this study is that RRI is a strategic instrument of the state in the non-military defense system. Through educational and informative functions that are carried out in a neutral and broad manner, RRI not only strengthens national resilience, but also provides a communication foundation that supports the sustainability of Indonesia's development and economic stability.